Analisa Angka Kapang dan Khamir Pada Lulur Bedda Lotong Dengan Penambahan Rumput Laut (Eucheuma cottonii) - Rahmawati Saleh; Andi Santi; Tasir Pammula; Ilham Ahmad; Ernawati Jassin; Afdalia Afdalia (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Bedda Lotong is a traditional scrub from the Bugis tribe of South Sulawesi, Indonesia. The name ‘Bedda Lotong’ literally means ‘black powder’ in Bugis language, referring to the distinctive black colour of this scrub which comes from its main ingredient, white glutinous rice that is roasted until burnt. The purpose of this study was to determine the number of colonies of moulds (thread moulds) and yeasts (one-celled fungi) in Bedda Lotong with the addition of Eucheuma cottoni seaweed. In addition, this study also aimed to determine the level of panellists' liking through organoleptic tests. The research design used was a factorial Completely Randomised Design (CRD) with 3 levels of treatment with 3 replications. The treatment of adding Eucheuma cottoni seaweed as a microbial growth inhibitor. Data processing was done with analysis of variance (ANOVA) test and continued with Duncan test using SPSS V.23 software. Based on the results of the study, it was obtained that the effect of the addition of Eucheuma cottoni seaweed did not significantly affect the ALT/TPC test (>0.05) (0.087) and had a significant effect (<0.05) (0.003) on the Bedda Lotong pH test and in the treatment of A1 (5%) and B1 (10%) seaweed concentrations gave organoleptic test scores from panellists, namely a score of 4 (like).